Abemaciclib treatment patterns and outcome in HR+/HER2- locally advanced or metastatic breast cancer: a real-world study from Kuwait and Lebanon - Al Nouri, Anwar; Al Terkait, Faisal; El Saghir, Nagi; Ghanem, Hady; Kattan, Joseph; Bishouti, Cynthia; Dreyer, Jade; Rai, Soniya; Rosca, Alexandru (Frontiers in Oncology, 2025)
PurposeThe burden of breast cancer is still growing in the Middle East and North Africa (MENA). BC patients typically present with more advanced stages than in Western countries. Limited information is available regarding the safety and efficacy of novel molecules for advanced BC in the Middle East region. The present real-world study evaluated the treatment patterns and survival outcomes of abemaciclib in patients with hormone receptor-positive (HR+)/human epidermal growth factor receptor-2-negative (HER2-) locally advanced or metastatic BC (mBC) in Kuwait and Lebanon.MethodsThe TRACE study is an observational, retrospective, multicenter, single-arm cohort study. Medical records of HR+/HER2- locally advanced or mBC women were retrieved if they received abemaciclib as part of their treatment in Kuwait and Lebanon. Only patients who received abemaciclib monotherapy or in combination with other treatments for at least three months before data collection were included.ResultsEighty-five patients met the eligibility criteria (Kuwait =42 patients, Lebanon =43). Nearly 57% of the patients received abemaciclib in the first-line setting, 19.8% received it in the second-line, and 16.5% received it at third or later lines of treatment. Abemaciclib 150mg twice daily was administered in combination with other treatments, mainly endocrine therapy, in 95.3% of the patients. Overall, 18 patients (21.4%) had a dose reduction at the end of the third month of abemaciclib treatment. After three months of treatment, the rates of complete response (CR) and partial response (PR) as the best response were 6.9% and 63.8%, respectively, with an objective response rate (ORR) of 70.7%. The 12-month progression-free survival (PFS) was 33.3% in the monotherapy group and 79.6% in the combination group.ConclusionThe present real-world evidence confirms the feasibility and effectiveness, in terms of response rate and PFS, of abemaciclib in patients with HR+/HER2- patients with locally advanced or mBC from Kuwait and Lebanon in the Middle East region.